LEGAL PROTECTION FOR VICTIMS OF BLOOD RAPE THAT PERFORM ABORTION - Hidayatulloh, Nofita Nurul; Isnawati, Muridah (IBLAM LAW REVIEW, 2022)
Inbreeding rape is rape committed by someone who is related by blood, such as father to child, uncle to nephew etc. Incest rape does not rule out the possibility of pregnancy in children and physical and psychological unpreparedness makes a child choose the path of abortion. So it is worth asking about the legality of abortion as referred to in Article 75 Paragraph 2 of Law Number 36 Year 2009 concerning Health if the one who performs the abortion is a child who is a victim of incest rape. Researchers use normative methods. The results of the study show that victims of incest rape who have abortions need a form of protection from the judge as a right that has been stated in the Child Protection Act, not as perpetrators of abortion. Pregnancy due to rape can cause psychological trauma for rape victims, therefore the law prohibits abortion unless there are signs of health problems that threaten the mother and/or fetus, as well as pregnancy due to rape, which can endanger the rape victim. Due to the disgrace and bad reputation of the family, children who have abortions (abortus provakatus) can be born with defects, although not all of them, women have the right to legal protection for their reproductive functions.